Changing Trends of Imaging in Angle Closure Evaluation. (13th May 2012) - Dorairaj, Syril; Tsai, James C.; Grippo, Tomas M.
Abstract : Primary angle closure glaucoma (PACG) is a significant cause of visual disability worldwide. It predominantly affects the Eastern and South Asian population of the world. Early detection of anatomically narrow angles is important, and the subsequent prevention of visual loss from PACG depends on an accurate assessment of the anterior chamber angle (ACA). Gonioscopy has given way to modern day imaging technologies such as ultrasound biomicroscopy (UBM) and more recently, anterior segment optical coherence tomography (AS-OCT). Ultrasound biomicroscopy provides objective, high-resolution images of anterior segment anatomy, including the cornea, iris, anterior chamber, anterior chamber angle, and ciliary body. Optical coherence tomography (OCT) is a noncontact optical signal acquisition and processing device that provides magnified, high-resolution cross-sectional images of ocular tissues. Recent technological advances towards three-dimensional visualization broadened the scope of AS-OCT in ophthalmologic evaluation. Optical coherence tomography systems use low-coherence, near-infrared light to provide detailed images of anterior segment structures at resolutions exceeding that of UBM. This paper summarizes the clinical application of UBM and OCT for assessment of anterior segment in glaucoma.